Evolution and distribution of coal mines in Salanpur Block, District Paschim Bardhaman, West Bengal - Mahata, Sangita; Sharma, V. N. (National Geographical Journal of India, 2022)
The objectives of this paper are to describe an historical account that includes transfer of ownership, nationalisation and mining under public/private ownership. The results shows that the newly started coal mines consisting separate units were runing under private owners and later on taken by Coal Mines Authority Ltd (CMAL) under Coal Mines Nationalisation Act in 1973. Consequently, these collieries were brought under public ownership from private ownership. In 1975, these collieries were incorporated under Eastern Coalfields Limited (a subsidiary of Coal India Limited) for extracting coal that fall under the administrative control of Salanpur Area which is an administrative block of ECL. During post-nationalisation period these collieries registered a low production although ECL had considered both underground and opencast methods of working to augment production but decline trend was continued as reserve in working seams was exhausted and non-availability of land for further mining operation due to illegitimate demand from local people. To meet the growing demand of coal for energy sector and other use, mining under private companies has been approved by ECL and also granted mining leases for operation.